2021
DOI: 10.3390/pharmaceutics13070925
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of STAT3 by Stattic Ameliorates Clinical Symptoms and Reduces Autoinflammation in Myeloid, Lymphoid, and Neuronal Tissue Compartments in Relapsing–Remitting Model of Experimental Autoimmune Encephalomyelitis in SJL/J Mice

Abstract: Multiple sclerosis (MS) is an immune-mediated inflammatory disease that leads to demyelination and neuronal loss in the central nervous system. Immune cells of lymphoid and myeloid origin play a significant role in the initiation and amplification of neuronal inflammation in MS. STAT3 signaling plays a pivotal role in both myeloid and lymphoid immune cells, such as neutrophils and CD4+ T cells, through regulation of their inflammatory potential. Dysregulation in STAT3 signaling in myeloid and lymphoid cell com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 57 publications
(118 reference statements)
0
16
0
Order By: Relevance
“…Finally, it is important to underscore that changes in expression/activity of both Stat3 and Socs3 are shown to affect clinical severity of MS/EAE. Pharmacological inhibition of Stat3 (Dang et al 2021;Alhazzani et al 2021) and, more important in respect of our study, the conditional deletion of Stat3 in myeloid cells (Lu et al 2020), have been shown to ameliorate and abrogate symptoms of EAE, respectively. The beneficial effects of these experimental treatments/procedures on EAE development partly or entirely (conditional deletion of Stat3 in myeloid cells) have been ascribed to impaired antigen presentation by myeloid cells and their diminished capacity to drive differentiation of pathogenic Th17 cells.…”
mentioning
confidence: 56%
“…Finally, it is important to underscore that changes in expression/activity of both Stat3 and Socs3 are shown to affect clinical severity of MS/EAE. Pharmacological inhibition of Stat3 (Dang et al 2021;Alhazzani et al 2021) and, more important in respect of our study, the conditional deletion of Stat3 in myeloid cells (Lu et al 2020), have been shown to ameliorate and abrogate symptoms of EAE, respectively. The beneficial effects of these experimental treatments/procedures on EAE development partly or entirely (conditional deletion of Stat3 in myeloid cells) have been ascribed to impaired antigen presentation by myeloid cells and their diminished capacity to drive differentiation of pathogenic Th17 cells.…”
mentioning
confidence: 56%
“…Moreover, highly activated STAT3 in T cells of clinically isolated syndrome (CIS) patients can predict the possibility of progression to MS ( 29 ). In addition, elevated STAT3 in brain myeloid cells was observed in MS patients and experimental autoimmune encephalomyelitis (EAE) model, proving its vital contribution to the regulation of myeloid cell function ( 30 , 31 ). Moreover, selective ablation of STAT3 made mice resistant to EAE induction by inhibiting the production of pathogenic T cells ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, elevated STAT3 in brain myeloid cells was observed in MS patients and experimental autoimmune encephalomyelitis (EAE) model, proving its vital contribution to the regulation of myeloid cell function ( 30 , 31 ). Moreover, selective ablation of STAT3 made mice resistant to EAE induction by inhibiting the production of pathogenic T cells ( 31 ). Immunohistochemical analysis of labial salivary gland (LSG) in SS patients showed that the expression of JAK1 and JAK2 was enhanced in ductal cells and acinar cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the activation of STAT3 signaling, a downstream effector of the ERK pathway, is also regulated by MDL 72527 treatment. STAT3 signaling is demonstrated to be a major player in EAE-induced [ 79 ] tissue damage [ 93 , 94 , 95 , 96 , 97 ]. The impact of MDL 72527 indicated in the present study supports the potential of SMOX inhibition in reducing inflammation, in addition to neuroprotection.…”
Section: Discussionmentioning
confidence: 99%